Impact of foliar application of syringic acid on tomato (Solanum lycopersicum L.) under heavy metal stress-insights into nutrient uptake, redox homeostasis, oxidative stress, and antioxidant defense - Ma, Jing; Saleem, Muhammad Hamzah; Ali, Baber; Rasheed, Rizwan; Ashraf, Muhammad Arslan; Aziz, Humera; Ercisli, Sezai; Riaz, Sana; Elsharkawy, Mohsen Mohamed; Hussain, Iqbal; Alhag, Sadeq K.; Ahmed, Ahmed Ezzat; et al. (Frontiers in Plant Science, 2022)
Soil contamination stimulated by metal stress is becoming a major issue now a days because it’s polluting our ecosystem. Elevated levels of lead (Pb) in agricultural lands hinder the rate of seed germination and impart detrimental impacts on physio-biochemical processes of plants. In this research, impact of two different concentrations of Pb (0, 50 and 100 mg L-1) on growth, biomass, photosynthetic activities, nutrients uptake, synthesis of ROS, concentration of various antioxidants, exclusion of organic acid and Pb accumulation in fruits, shoots, roots and leaves was investigated under exogenous treatment of syringic acid [no spray (NS), water spray (WS), 0.3-0.5 µM] in two tomato (Solanum lycopersicum L.) varities (Roma and Cchuas). Our results illustrated that soil spiked with Pb reduced significantly (P < 0.05) the growth, chlorophyll contents, gas exchange parameters and assimilation of essential nutrients in S. lycopersicum in comparison to soil which was not added with Pb. We concluded that Cchuas showed better growth and tolerance potential than Roma under Pb metal stress. However, Pb toxicity enhanced pointers of stress such as MDA, H2O2 and EL, organic acid exudation, enzymatic antioxidants like SOD, POD and CAT, non-enzymatic antioxidants such as phenolic, flavonoid, ascorbic acid and anthocyanin and Pb contents in shoots, roots and leaves of S. lycopersicum. Results also revealed that contents of proline, free amino acids, soluble and reducing sugars also enhanced in plants treated with Pb in comparison to those tomato plants not added with Pb. Furthermore, results also showed that exogenous application of syringic acid (0.3-0.5 µM) contribute significantly in the alleviation of Pb toxicity in S. lycopersicum. So, syringic acid can be applied to those agricultural fields which are facing heavy metal toxicity.